A Simple and Effective Bio-adsorbent Generated from the Stems of Momordica charantia Plant for the Simultaneous Removal of Lead and Cadmium Ions from Wastewater - Babu Vabanagiri, Rajesh; Ravindhranath, Kunta; Latha Pala, Sneha; Kebede Biftu, Wondwosen (Asian Journal of Chemistry, 2021)
Sulphuric acid generated activated carbon from the stems of Momordica charantia (MCSAC) was identified to adsorb lead(II) and cadmium(II) ions from water. Extraction conditions were optimized. At pH: 6, both the ions can be simultaneous removed by 2.0 mg/L of MCSAC after an equilibration period of 90 min at room temperate (30 ± 2 ºC). The sorption capacities were observed to be 21.0 mg/g for Pb2+ and 18.9 mg/g for Cd2+. MCSAC was characterized by conventional methods and also by surface morphology assessing techniques such as XRD, FTIR and FESEM. The sorption mechanism was investigated by evaluating thermodynamic parameters and by adopting various kinetic and isothermal models. High ΔH values of 29.399 KJ/mol for Pb2+ and 33.222 KJ/mol for Cd2+, indicated that the mechanism of sorption is ion exchange and /or complex formation between Pb2+/Cd2+ ions and surface functional groups present in MCSAC. Further, high positive ΔS values imply the presence of disorder at solid-liquid interface, favouring the metal ions to overcome the surface barrier and get adsorbed. The negative ΔG values indicates the spontaneity of sorption process. Spent MCSAC can be regenerated and reused for three cycles. The procedure developed using MCSAC as sorbent was successfully applied to treat real effluents samples collected from several industrial effluents. The novelty of the present investigation is that a simple biosorbent is developed for the effective simultaneous removal of highly toxic Pb2+ and Cd2+ from contaminated water.